Possible Risk Assessment of Dementia Due to Air Pollution in Czech Republic - J. Topinka; P. Rossner; A. Rossnerova; R. J. Sram (Current Overview on Disease and Health Research Vol. 9, 2023)
A review of recent literature indicates a significant effect of air pollution on the increased incidence of dementia, particularly Alzheimer’s disease. Dementia, encompassing both vascular dementia and Alzheimer’s disease, is now reported as the leading cause of death in England and Wales, accounting for 12% of all registered deaths. Ambient air pollution is a pervasive and ubiquitous hazard, which has been linked to premature morbidity and a growing number of morbidity endpoints. Air pollution may be linked to neurodegeneration, and via this or other pathways, to neurodegenerative diseases. Inflammation and oxidative damage are two potential mechanisms. The mining regions of Northern Bohemia in the Czech Republic experienced extremely high air pollution levels in previous decades, and during the most recent period, Northern Moravia also experienced this issue. By combining cutting-edge molecular epidemiology techniques with a thorough examination of the lifestyle choices of the population residing in polluted areas, this specific situation could be used to study the relationship between air pollution and dementia.